(untitled) (Journal of Environmental Science and Natural Resources, 2016)
A study was conducted to determine the poverty and credit facilities of groundnut producers and profitability and resource use efficiency of groundnut production in the selected char areas of Gaffargaon upazila in Mymensingh district. In this study, 100 respondents were randomly selected from the mentioned upazila. Farmers were classified into three categories on the basis of loan size. Cobb-Douglas production function was used to determine the contribution of factors to groundnut yield. It is evident from the study that per acre net returns were greatly influenced by the use of human labour, animal labour, seeds and insecticides and it was found that they got profit from groundnut cultivation and the undiscounted BCRs (both the variable cost and total cost basis) was estimated at 1.88 in case of all categories of farmers. The mentioned factors were directly or jointly responsible for influencing per acre net returns for groundnut cultivation. Maximum loan money was utilized in family expenditure purpose for meeting their emergency and urgent needs to survive. But their repayment was satisfactory. However some problems were identified (i.e, tips and bribes, delay in providing loan and their poverty) in receiving loan for groundnut cultivation. It appears from the analysis that among three categories of farmers marginal farmers suffered a lot from inadequate supply of credit. The present study suggests that to develop agriculture, to reduce poverty and to increase the productivity of the farmers, both public and private sectors need to give attention on groundnut production in char area for their poverty reduction. J. Environ. Sci. & Natural Resources, 8(2): 57-62 2015